Breaking the trade-off: Trichoderma effector Tahfb1 dual-targets growth and defense pathways via Hsp70L - Yaping Yin; Yuhang Fu; He Wu; Liping Feng; Lijuan He; Runmao Lin; Rui Wang; Zhengbin Tang; Baoping Zhu; Jumei Hou; Jing Zhao; Tong Liu (Pesticide Biochemistry and Physiology, 2026)

Comparative transcriptomics of susceptible and resistant Cucumis metuliferus upon Meloidogyne incognita infection - Xiaoxiao Xie; Junru Lu; Runmao Lin; Jian Ling; Zhenchuan Mao; Jianlong Zhao; Qihong Yang; Shijie Zheng; Yan Li; Richard G. F. Visser; Yuling Bai; Bingyan Xie (Planta, 2025)

Characterization and evaluation of the morphological attributes of Ethiopian mustard (Brassica carinata A. Braun) landraces - Rahiel Hagos Abraha; Abdulwahab S. Shaibu; Jianli Liang; Jian Wu; Runmao Lin; Xiaowu Wang (Euphytica, 2024)
Ethiopian mustard ( Brassica carinata A. Braun) is one of the Brassica leafy vegetables and oilseed crops, which can withstand adverse environmental conditions. This study was conducted to characterize and evaluate the leaf attributes of 313 Ethiopian mustard accessions grown in the greenhouse and field in 2018/19 in Beijing, China. Data on 18 different leaf morphological attributes were collected based on the IBPGR for Brassica and Raphanus descriptor format and Fiji Image J. The collected data were subjected to descriptive statistics using JMP version 14 software. Results indicate that the majority of the accessions had serrated leaf margin, intermediate juvenile development, rounded apex leaf shape, absence of leaf pubescence, number of lobes > 5 and had intermediate number of leaves per plant with frequencies of 101, 213, 223, 244, 183 and 289, respectively. The accessions had also white midrib color, light green leaf color, purple petiole color, purple stem color and purple apex leaf color pigments with frequencies of 168, 165, 104, 113 and 122, respectively. Significant differences were observed among the accessions for leaf size attributes ( p < 0.001) indicating their potential as leafy vegetables. Furthermore, there were significant accession × environment effects for the laminal length, total leaf length, leaf area, leaf weight and petiole length. Notably, 71% of the accessions had an average of 81 days flowering time. The multivariate cluster and principal component analyses divided the 313 accessions into eight groups with distinctive information; consisting of 81, 37, 79, 38, 14, 11, 6 and 47 accessions. Thus, this study provides important information about Ethiopian mustard germplasms that is vital for further advancement and genetic improvement of the crop.

Correction: Improved Brassica oleracea JZS assembly reveals significant changing of LTR‑RT dynamics in different morphotypes - Xu Cai; Jian Wu; Jianli Liang; Runmao Lin; Kang Zhang; Feng Cheng; Xiaowu Wang (Theoretical and Applied Genetics, 2023)

Efficient detection and picking sequence planning of tea buds in a high-density canopy - Guichao Lin; Juntao Xiong; Runmao Zhao; Xiaomin Li; Hongnan Hu; Lixue Zhu; Rihong Zhang (Computers and Electronics in Agriculture, 2023)

Improved Brassica oleracea JZS assembly reveals significant changing of LTR-RT dynamics in different morphotypes - Xu Cai; Jian Wu; Jianli Liang; Runmao Lin; Kang Zhang; Feng Cheng; Xiaowu Wang (Theoretical and Applied Genetics, 2020)

Sequencing, annotation and comparative analysis of nine BACs of giant panda (Ailuropoda melanoleuca) - Yang Zheng; Jing Cai; JianWen Li; Bo Li; Runmao Lin; Feng Tian; XiaoLing Wang; Jun Wang (Science China Life Sciences, 2010)